Two new species of the genus Laena Dejean (Coleoptera: Tenebrionidae: Lagriinae) from Hong Kong - Schawaller, Wolfgang; Aston, Paul (Zootaxa, 2017)
Two new species of the genus Laena Dejean, 1821 (Coleoptera: Tenebrionidae: Lagriinae) are described from Hong Kong: Laena hongkongica sp. n. and Laena walkeri sp. n. These constitute the first record of the genus from Hong Kong, as a species previously described from nearby area Laena ovipennis Schuster, 1926, in fact originated from Zhejiang province nearby Shanghai. Both species from Hong Kong possess a wide variation in body length, which is quite unusual for this genus.